Efficacy and safety of different JAK inhibitors in the treatment of alopecia areata: a network meta-analysis - Wei, Dongfan; Chen, Yi; Shen, Yuqing; Xie, Bo; Song, Xiuzu (Frontiers in Immunology, 2023)
Background Alopecia areata (AA) is an immune disease characterized by non-scarring hair loss. With the widespread application of JAK inhibitors in immune-related diseases, attention is being given to their role in the treatment of AA. However, it is unclear which JAK inhibitors have a satisfactory or positive effect on AA. This network meta-analysis aimed to compare the efficacy and safety of different JAK inhibitors in the treatment of AA. Methods The network meta-analysis was performed according to the PRISMA guidelines. We included randomized controlled trials as well as a small number of cohort studies. The differences in efficacy and safety between the treatment and control groups were compared. Results Five randomized controlled trials, two retrospective studies, and two prospective studies involving 1689 patients were included in this network meta-analysis. In terms of efficacy, oral baricitinib and ruxolitinib significantly improved the response rate of patients compared to placebo [MD = 8.44, 95% CI (3.63, 19.63)] and [MD = 6.94, 95% CI, (1.72, 28.05)],respectively. Oral baricitinib treatment significantly improved the response rate compared to non-oral JAK inhibitor treatment [MD=7.56, 95% CI (1.32,43.36)]. Oral baricitinib, tofacitinib, and ruxolitinib treatments significantly improved the complete response rate compared to placebo [MD = 12.21, 95% CI (3.41, 43.79)], [MD = 10.16, 95% CI (1.02, 101.54)], and [MD = 9.79, 95% CI, (1.29, 74.27)], respectively. In terms of safety, oral baricitinib, tofacitinib, and ruxolitinib treatments significantly reduced treatment-emergent adverse event rates compared with conventional steroid treatment [MD = 0.08, 95% CI (0.02, 0.42)], [MD = 0.14, 95% CI (0.04, 0.55)], and [MD = 0.35, 95% CI, (0.14, 0.88)], respectively. Conclusion Oral baricitinib and ruxolitinib are excellent options for the treatment of AA owing to their good efficacy and safety profiles. In contrast, non-oral JAK inhibitors do not appear to have satisfactory efficacy in treating AA. However, further studies are required to verify the optimal dose of JAK inhibitors for AA therapy.